DISORDER OF KIDNEY FUNCTION IN PATIENTS WITH COMORBIDITY AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The review describes the pathogenetic mechanisms of the two-way effect of the general systemic manifestations of chronic obstructive pulmonary disease (COPD) and chronic kidney disease (CKD) in comorbid situations. Most systemic manifestations of COPD, such as anemia, depression, mineral-bone disorders, cardiovascular complications, coincide with manifestations of CKD and can be mistakenly considered only as manifestations of COPD. Mechanisms underlying heart remodeling and the progression of CKD in COPD are distinguished, such as hypoxemia, systemic inflammation, endothelial dysfunction, activation of the sympathetic nervous and renin-angiotensin-aldosterone systems, oxidative stress, and prolonged endogenous intoxication.